US-China trade war and its impact on German automotive sector - Varga, Michal (2025)
This thesis examines the impact of the US-China trade war on Germany’s automotive sector, with a focus on political risk and international business implications. As the third-largest economy globally, Germany—highly dependent on exports—serves as a case study for evaluating the indirect consequences on third countries of major bilateral trade conflicts. The study utilizes a mixed-methods approach, combining macroeconomic indicators with firm-level data from Volkswagen, BMW, and Mercedes-Benz, to assess how tariffs, disrupted supply chains, and geopolitical shifts affected revenues, market share, and production strategies. The analysis reveals that although the German automotive sector experienced resilience in revenue, it faced significant challenges including reduced vehicle sales, increasing Chinese competition, and rising production costs. Companies adopted various strategic responses, such as diversification, investment in R&D, and vertical integration to mitigate these risks. Findings underscore the necessity for adaptive business strategies in volatile geopolitical environments and highlight the broader implications of trade wars on non-participant nations. This research contributes to the understanding of political risk in global value chains and offers practical insights for businesses navigating complex international trade dynamics.